Surya - Temples of India Project Team (Jio Institute, 2024)
This majestic image of Surya must have once been placed inside the sanctum of a lost Surya shrine. Coupled with multiple other Surya images at the shrine (Surya, Chhaya, etc.), it suggests the maturity of Surya tradition at the hill, which was present at the hill at least from the eight century - much before the emergence of Harshadeva-Shiva as the royal shrine at the hill. He is holding two fully bloomed lotuses in each hand. He is flanked on either side by his companions, Danda and Pingala, immediately near his legs, and the pair of horse-faced Ashvin brothers, at the back. On the above register is an elegant pair of bow holders about to unleash an arrow. Surya is wearing a kirita-mukuta and the halo in the form of a fully bloomed lotus appropriately suits the radiant glow of the majestic Sun God.